2021
DOI: 10.3390/ijerph182212246
|View full text |Cite
|
Sign up to set email alerts
|

Nature Exposure and Positive Body Image: A Cross–Sectional Study Examining the Mediating Roles of Physical Activity, Autonomous Motivation, Connectedness to Nature, and Perceived Restorativeness

Abstract: Research shows that nature exposure is directly and indirectly associated with more positive body image, which is an important facet of well-being more generally. In this study, we tested the mediating roles of physical activity in nature, perceived restoration in nature, autonomous motivation, and connectedness to nature in explaining the association between nature exposure and positive body image. An online sample of 924 Lithuanian adults (age M = 40.0 years, 73.6% women) completed a survey that included the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 76 publications
(130 reference statements)
2
7
0
1
Order By: Relevance
“…For this analysis, we only used the RAI calculated by the equation (−3 × amotivation) + (−2 × external motivation) + (−1 × introjected motivation) + (2 × identified motivation) + (3 × intrinsic motivation), where a higher score indicates more autonomy in exercise regulation, and a lower score indicates more controlled regulation and/or amotivation for exercise [ 61 ]. The original five-factor structure of the Lithuanian translation of the BREQ-2 was confirmed in our previous studies in general adult populations [ 62 , 63 ].…”
Section: Methodssupporting
confidence: 72%
“…For this analysis, we only used the RAI calculated by the equation (−3 × amotivation) + (−2 × external motivation) + (−1 × introjected motivation) + (2 × identified motivation) + (3 × intrinsic motivation), where a higher score indicates more autonomy in exercise regulation, and a lower score indicates more controlled regulation and/or amotivation for exercise [ 61 ]. The original five-factor structure of the Lithuanian translation of the BREQ-2 was confirmed in our previous studies in general adult populations [ 62 , 63 ].…”
Section: Methodssupporting
confidence: 72%
“…In the current study, following self-compassion, with a substantially smaller effect size, connectedness with nature also took part in explaining the variance in participants’ body appreciation. This is in line with previous research highlighting that both exposure to natural environment [ 50 , 51 ] and a sense of connectedness with nature were associated with higher body appreciation among both males and females [ 52 ]. Interestingly, recent research has reported how the specific natural environment matters.…”
Section: Discussionsupporting
confidence: 92%
“…In the first instance, this stands in contrast to studies showing that perceptions of the qualities of an environment are associated with greater restoration and psychological well-being [ 27 , 41 , 42 ]. In the second instance, the null effect vis-à-vis subjective restoration stands in contrast to the predictions of attention restoration theory [ 21 , 22 ] as well as cross-sectional work showing that recalled restoration is significantly associated with body appreciation [ 10 ]. One explanation for the present findings is that environmental factors may not exert much of an effect on state body appreciation changes in natural environments once the effects of dispositional traits have been accounted for.…”
Section: Discussionmentioning
confidence: 88%
“…The evidence base supporting an association between nature and a positive body image has three main sources. First, cross-sectional studies [ 10 , 11 , 12 , 13 , 14 ] and an experience sampling study [ 15 ] have shown that self-reported nature exposure is significantly associated with multiple indices of the traits of a positive body image, including body appreciation and functionality appreciation. Second, experimental studies have shown that exposure to both real and simulated (i.e., images or film) natural environments results in an elevated state body appreciation [ 11 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation